A QUALITATIVE STUDY ON ACCESS BARRIERS TO MENTAL HEALTHCARE SERVICES BY SYRIAN REFUGEE WOMEN IN WINNIPEG, MANITOBA, CANADA - Sanjida Newaz (Rojan GÜMÜŞ, 2020)
The world refugee crisis is currently at a record level. Refugees have an increased risk of developing mental illness like post-traumatic stress disorder (PTSD), depression, and somatic symptoms because of their exposure to violence. Despite increased healthcare needs, refugees face considerable barriers in accessing services. Women refugees may have unique mental healthcare needs due to their vulnerability to gender-based violence and abuse during flight from war. This study explores the mental healthcare need, availability of support and barriers in accessing services among Syrian refugee women in Winnipeg. Semi-structured interviews were conducted with nine refugee women and six service providers/decision makers. The data were analyzed using a qualitative thematic approach aided by NVivo 12 qualitative software. The most cited barriers in accessing mental healthcare services were language, weather, unemployment, stigma, system navigation, different understandings of mental health and illness, and lack culturally competent care. Results from this study can inform decision makers of issues requiring policy responses to improve mental healthcare for refugee women in Manitoba.